Improving Student’s Motivation and Learning Outcomes Through Genetics E-Module - Fidiastuti, Hasminar Rachman; Lathifah, Anis Samrotul; Amin, Mohamad; Utomo, Yudhi; Aldya, Riantina Fitra (Jurnal Ilmiah Peuradeun, 2021)
The purpose of this study was to know the impact of the Genetics E-module to improve students’ motivation and learning outcomes during the learning process. The method applied was Research and Development, limited until the implementation stage, using the quasi-experiment method with one group pretest-posttest. The motivation instruments were modified questionnaire by Keller with ARCS model, consist of 4 aspects including attention, relevance, confidence, and satisfaction. The population were all of the students from class of 2017 in Biology Education department, Tribhuwana Tunggadewi State University. The pretest was held to know students’ motivation and learning outcomes when using a handout from the lecturer, while the posttest was to know students’ motivation and learning outcomes when using Genetics E-module. Data were collected from the motivation questionnaire and test. After using E-module, there were 27 students with high (71,91 ≤ x < 86), 18 students with medium (57,82 ≤ x < 71,91) and 5 students with low criterion (43,74 ≥ x) of motivation, and there were 58% students who passing the grade in Genetics test. Based on the data analysis, E-module was feasible to be used to improve students’ motivation and also learning outcomes in the Biology Education department.